BUSINESS STRATEGIES AND INNOVATION ON COMPETITIVE ADVANTAGE OF SMEs - Ahmad Zaini (Scientia Integritas Utama, 2023)
In the face of a dynamic and competitive environment, SMEs must figure out how to remain competitive. This has to do with SMEs' future growth and survival. The purpose of this study was to investigate how innovation and business strategy affect competitive advantage. 68 questionnaires were used to gather information. In the Makassar city fresh market, 68 SME owners received a total of questionnaires. the probability sampling approach used to select the sample. Multiple Linear Regression with SPSS version 23 was used to analyze the data. Business strategy and innovation have a positive and significant impact on competitive advantage, according to this study's findings.